The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/app6110319
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Glycyrrhizic Acid from Glycyrrhiza uralensis Using Ultrasound and Its Process Extraction Model

Abstract: This work focused on the intensification of extraction process of glycyrrhizic acid (GA) from Glycyrrhiza uralensis using ultrasound-assisted extraction (UAE) method. Various process parameters such as ultrasonic power, ultrasonic frequency, extraction temperature, and extraction time which affect the extraction yield were optimized. The results showed that all process parameters had exhibited significant influences on the GA extraction. The highest GA yield of 217.7 mg/g was obtained at optimized parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The primary aqueous extract from liquorice roots contains GA and many other water-soluble substances, which are then subjected to further process more purified products. Pure GA is also prepared from liquorice roots using alcohol as the extraction solvent in an ultrasonic device, followed by purification [ 126 ]. The conventional solvent extraction technique followed to extract GA from liquorice offers several disadvantages, namely considerable solvent requirements, longer extraction time, lower yields and higher extraction temperature.…”
Section: Production Of Safe Enviro-friendly Natural Sweetenersmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aqueous extract from liquorice roots contains GA and many other water-soluble substances, which are then subjected to further process more purified products. Pure GA is also prepared from liquorice roots using alcohol as the extraction solvent in an ultrasonic device, followed by purification [ 126 ]. The conventional solvent extraction technique followed to extract GA from liquorice offers several disadvantages, namely considerable solvent requirements, longer extraction time, lower yields and higher extraction temperature.…”
Section: Production Of Safe Enviro-friendly Natural Sweetenersmentioning
confidence: 99%
“…The conventional solvent extraction technique followed to extract GA from liquorice offers several disadvantages, namely considerable solvent requirements, longer extraction time, lower yields and higher extraction temperature. All this requires developing an effective economical extraction method [ 126 ]. The purification procedure involves the acidification of the extract by adding acids like H 2 SO 4 or HCl acids to form the solid product of GA salt (at pH 1–2).…”
Section: Production Of Safe Enviro-friendly Natural Sweetenersmentioning
confidence: 99%
“…Glycyrrhizin has medicinal properties in humans including antioxidant and anti-cancer, anti-viral, anti-hepatitis, anti-skin allergies, antiinflammatory, anti-wound, and anti-peptic ulcers. Glycyrrhizin is also used as a food sweetener (Tian et al, 2008;Shabani et al, 2009;Liao et al, 2016).…”
Section: Preparation Of Standards and Calibration Curvesmentioning
confidence: 99%
“…Many techniques have been used to extract bioactive compounds from liquorice samples. For instance, Liao et al (2016) isolated GL from G. uralensis by using an ultrasonic bath system. Shabkhiz et al (2016) found that superheated water extraction had a relatively higher efficiency than a Soxhlet extractor and UAE for obtaining GL from liquorice roots and, like Hedayati and Ghoreishi (2015), used the response surface methodology (RSM) strategy to optimise extraction conditions.…”
Section: Introductionmentioning
confidence: 99%